Mobile mindfulness : a comparative study of mindfulness and relaxation apps, and the impact on employee wellbeing in the workplace : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Manawatū, New Zealand - Buckman, Antonia (Massey University, 2019)
Organisations are looking for effective interventions to improve employee wellbeing in order to counteract high work demands. Mindfulness has recently gained in popularity as a readily available tool that can be utilised for a variety of self-improvement and wellbeing effects. Technological advances in the mobile health space have placed mindfulness interventions onto smartphone devices allowing anyone, anywhere, to access such tools. However, there remains a number of limitations on current research. This investigation explored the effectiveness of a mindfulness app within the workplace and its impact on employee wellbeing using both an active and waitlist control. A randomised semi-blind control trial was conducted with a diverse self-selecting sample, randomly assigned to one of three groups: mindfulness intervention, relaxation app active control, or passive waitlist control. Apps were used for three to five days per week over a four week period. Participants completed a baseline questionnaire (n = 95) measuring personality, mindfulness, and a range of wellbeing measures. Questionnaire was repeated at the end of the four week intervention (n = 67), and again four weeks post intervention (n = 52). The study explored impact of mindfulness on employee wellbeing, sustained benefits four weeks post intervention, effect of expectancy on intervention, impact on longer usage of intervention app, and impact of personality type in continuing the study and effect of the intervention. Results of repeated measure ANOVAs showed no significant effect of mindfulness on employee wellbeing, therefore no analysis was conducted of sustained results. Expectancy of the effectiveness of the trial positively correlated with self-rated perceived positive impact of the mindfulness intervention, but not for either control group. Length of time the app was used was not significant. There was a positive correlation between the intervention and the Positive subscale of Positive and Negative Affects Scale and negative correlations with the Autonomy and Self-Actualisation subscales of Ryff's Wellbeing Scales for the mindfulness intervention group, this differed to the active control group. There were no statistically significant changes in the waitlist passive control condition. Findings do not support the viability of smartphone-based mindfulness interventions to significantly improve employee wellbeing.
Keywords: Mindfulness (Psychology); Relaxation; Computer programs; Evaluation; Mobile apps; Employee health promotion; Well-being